Cost-effectiveness of rural energy access strategies - Jörg Ankel-Peters; Gunther Bensch; Kevin Moull; Mascha Rauschenbach; Maximiliane Sievert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Quantitative benchmarks for cost-effective provision of rural energy access are difficult to obtain because deployment costs vary across technologies, contexts, and technical assistance approaches - but crucially also across sustainability assumptions. As an alternative, this policy perspective provides a qualitative cost-effectiveness assessment of different energy access strategies. We discuss the different cost factors, accounting for differences in impact potentials across rural energy access options. We include on-grid and off-grid electrification and improved cooking technologies. The focus is on rural sub-Saharan Africa (SSA), where energy access rates are low. We document largely disappointing impacts of high-power electrification technologies, turning stand-alone solar into the more cost-effective electrification strategy in that setting. We conclude by emphasizing the high impact-cost ratio for energy-efficient biomass cookstoves. – – Quantitative Benchmarks für eine kosteneffiziente Bereitstellung von Energiezugang in ländlichen Gebieten sind schwer zu ermitteln, da die Bereitstellungskosten je nach Technologie, Kontext und Ansatz der technischen Hilfe variieren. Entscheidend ist auch, welche Annahmen hinsichtlich der Nachhaltigkeit getroffen werden. Als Alternative bietet diese politische Perspektive eine qualitative Bewertung der Kosteneffizienz verschiedener Strategien für den Zugang zu Energie. Wir diskutieren die verschiedenen Kostenfaktoren und berücksichtigen dabei die unterschiedlichen Wirkungspotenziale der Optionen für den Zugang zu Energie in ländlichen Gebieten. Dabei berücksichtigen wir sowohl netzgebundene als auch netzunabhängige Elektrifizierung sowie verbesserte Kochtechnologien. Der Schwerpunkt liegt auf dem ländlichen Subsahara-Afrika (SSA), wo die Energieversorgungsquote niedrig ist. Wir dokumentieren weitgehend enttäuschende Auswirkungen von Hochleistungselektrifizierungstechnologien, wodurch autonome Solaranlagen in diesem Umfeld zur kosteneffizienteren Elektrifizierungsstrategie werden. Abschließend betonen wir das hohe Wirkungs-Kosten-Verhältnis energieeffizienter Biomasse-Kochherde.
Keywords: H54; O21; O33; 330; Energy access; rural electrification; modern cooking energy; sub-Sahara Africa